2003
DOI: 10.1016/s1525-0016(03)00230-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-delivered angiopoietin-1 reduces the infarction and attenuates the progression of cardiac dysfunction in the rat model of acute myocardial infarction

Abstract: In acute myocardial infarction (AMI), prognosis and mortality rate are closely related to the infarct size and the progression of postinfarction cardiac failure. Angiogenic gene therapy has presented a new approach for the treatment of AMI. Angiopoietin-1 (Ang1) is a critical angiogenic factor for vascular maturation and enhances vascular endothelial growth factor (VEGF)-induced angiogenesis in a complementary manner. We hypothesized that gene therapy using Ang1 for AMI might promote angiogenesis cooperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 46 publications
5
63
1
Order By: Relevance
“…Transplantation of hMSCs leads to a significantly improved function in the post-infarction left ventricle. Angiopoietin-1 has been shown to enhance angiogenesis and to attenuate progression of cardiac dysfunction after myocardial infarction [16,17]. In our study, the angiogenesis effect of Ang1 was not obvious.…”
Section: Discussioncontrasting
confidence: 57%
“…Transplantation of hMSCs leads to a significantly improved function in the post-infarction left ventricle. Angiopoietin-1 has been shown to enhance angiogenesis and to attenuate progression of cardiac dysfunction after myocardial infarction [16,17]. In our study, the angiogenesis effect of Ang1 was not obvious.…”
Section: Discussioncontrasting
confidence: 57%
“…1,2 Nevertheless, newly formed vessels in the above studies were mainly capillaries whose efficacy in improving blood perfusion was inconclusive. For instance, Hershey et al 3 reported that newly formed vessels induced by VEGF were insufficient for the improving of collateral blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…ANG-1 has been reported to significantly increase arteriolar density and reduce infarct size leading to improved cardiac performance following AMI in rodent models [42,43]. Furthermore, ANG-1 has been suggested to enhance hemodynamics by forming more complex vascular network characterized by mature vessels of increased luminal size [44,45].…”
Section: Discussionmentioning
confidence: 99%